Perlindungan Hak Penyandang Disabilitas Untuk Memperoleh Pekerjaan Dan Penghidupan Yang Layak - Ismiraj, Muzaki; Subroto, Mitro (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2023)
Seeing the existing regulations in the 1945 Constitution, it is stated that it will provide legal guarantees and protection to all Indonesian people, including work and a decent living for humanity, without exception, namely persons with disabilities. The problem here is that there are still many people with disabilities who experience discrimination against themselves and the education they take is also still below average. This provides a considerable distance between persons with disabilities and nondisabled persons. When we see or mention Indonesia, we immediately see that it is a country that upholds human rights. This form of human rights protection is an obligation for the Indonesian government. The purpose of this research is to find out how to fulfill human rights for workers with disabilities to survive in their lives. The research method is qualitative with a normative legal approach and juridical sociology. The results of the study stated that the fulfillment of human rights, especially the fulfillment of the right to work for persons with disabilities, had not been fully implemented. Because there are still many conflicts or weak regulations in the government. This is very important to be used as an improvement and commitment by the government so that people with disabilities can get decent jobs and livelihoods.